Extractive industry employment in Peru: A geographical or spatial analysis - Tello, Mario D. (2018)
This paper estimates the spatial or geographic effects of employment, income and production value of eleven mining centers upon the share of employment of the primary, secondary and tertiary sectors from the geographic areas wherein these centers are located. Based upon a Spatial Durbin Model, SDM, the main estimation results points outs that the ‘direct effects’ of the income or mining output generated in the geographic areas wherein the mining centers are located upon the share of employment in the primary, secondary and tertiary sectors of the same areas were statistically significative for most of the estimations (about 69,4% of them). Contrarily, these effects for the share of formal employment of the mining centers were not statistically significative for most of the estimations (about 61,1% of them). However, the ‘indirect’ geographic or spillovers effects of such an employment were significative particularly for the share of the informal employment of the secondary, tertiary and primary (in that order). These employment geographic spillovers effects has implied that changes in the formal employment share in the mining sectors were associated to changes in the informal employments shares of the secondary, tertiary and primary (in that order) of the geographic areas close to de mining production centers. The indirect effects of income and production value in the production centers were not significative.